Influence of Stainless Steel Mesh Size and Universal Adhesive Primer on Flexural Strength of Repaired PMMA Denture Base Resin - Gray H. Li; Vidya Mudaliar; Andrew B. Cameron; John M. Aarts; Joanne J. E. Choi (Clinical and Experimental Dental Research)
ABSTRACT Objectives To evaluate the effect of the size of stainless steel mesh and universal adhesive primer on the flexural strength of repaired polymethylmethacrylate (PMMA) denture base resin. Materials and Methods A total of 120 heat‐cured PMMA specimens with dimensions of 5 × 50 × 30 mm were prepared and repaired with two different sizes of stainless steel mesh reinforcement, one group with med‐fine mesh (size 0.42 mm2) and the second group with fine mesh (size 0.09 mm2). One subgroup was primed with a universal adhesive primer (Scotchbond Universal). Half of the specimens from each subgroup were subjected to artificial aging. The flexural strength was obtained by three‐point bend testing. Data were statistically analyzed using ANOVA and post hoc analysis (SPSS V28). The probability of failure was calculated using Weibull analysis. Scanning electron microscopy analysis was used to identify the mode of failure. Results A significantly higher mean flexural strength (p < 0.05) was recorded in primed groups non‐thermocycled with fine mesh (174.80 ± 50.27 MPa) and medium mesh (160.87 ± 41.50 MPa) compared to non‐primed groups. Non‐primed specimens with fine mesh exhibited the highest Weibull modulus (5.86), whereas that of primed medium mesh had the lowest Weibull modulus (2.64). Adhesive failure was identified at the interface of the stainless steel mesh and the self‐cure acrylic resin. Conclusion Application of the universal adhesive primer to both mid‐fine and fine stainless steel mesh significantly improved the flexural strength of the repaired PMMA heat‐cured acrylic resin, and reinforcement with primed fine stainless steel mesh resulted in significantly higher flexural strength of repaired PMMA heat‐cured an acrylic resin.